Knowledge and Teaching Practices of Islamic Education Teachers in Learning Female Blood Fiqh of Secondary School Islamic Education Curriculum: Analysis Based on Contextual Learning Approach - Yaakob, Siti Falihah Binti; Tengku Kasim, Tengku Sarina Aini Binti; Mohd Razif, Nor Fahimah Binti; Al Maawali, Iman Mohammed Zaid (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2025)
Teachers need to possess certain information in order to teach a class properly, particularly when teaching Worship and Fiqh, which includes memorization of practices, legal issues, fardu ain, and fardu kifayah, as well as student appreciation. Since teaching worship involves legal concerns and issues, it is crucial for teachers to be well-versed in the subject matter because this will affect both the pedagogical strategies they use to deliver the lesson's content and their ability to meet the established learning objectives. But according to the researcher's analysis, there are a number of holes in the Malaysian Secondary School Standard Curriculum (KSSM), namely in the area of worship that deals with women's blood instruction. Lack of exposure to and in-depth discussion of this subject impairs instructors' fundamental comprehension of women's blood, making it difficult for them to tackle the blood problems that students face in the classroom. Subsequently, the purpose of this article is to examine the methods and understanding of Islamic Education instructors about the fiqh of women's blood as taught in the Malaysian Secondary School Standard Curriculum (KSSM). The data for this qualitative study was gathered through semi-structured individual interviews with four Islamic Education Teachers (GPIs) who are now employed by the Malaysian Ministry of Education (KPM) in National Secondary Schools. The teachers were chosen by purposive sampling. Interview data has been analysed based on the idea of a contextual learning method to investigate how much teachers' practices and knowledge promote students' contextual learning characteristics. The study's findings indicate that Islamic Education teachers are still not fully utilising the contextual learning approach when it comes to women's blood because of their limited understanding of the subject and the Malaysian Secondary School Standard Curriculum (KSSM) coverage of the subject matter. Since teachers are responsible for imparting knowledge to their students, it is important to highlight the importance of teachers' ongoing pursuit of knowledge. This will help teachers become more knowledgeable about the subjects they teach and will also enable them to respond to inquiries from students promptly.